1963
DOI: 10.1677/joe.0.0260139
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of [4-14c]-Progesterone by Adrenocortical Tissue From Patients With Cushing's Syndrome

Abstract: The metabolism of [4-14C]-progesterone in vitro by adrenocortical tissue from three patients with Cushing's syndrome has been studied. The glands of two of these patients were hyperplastic and the third patient, a severely virilized girl, had a large adrenal tumour. Slices taken for study from the hyperplastic glands contained 'clear' fascicular and 'compact' reticular cells. The tumour slices were 'clear' cells.The major metabolites in each case were 17\g=a\-hydroxyprogesterone, 16\g=a\-hydroxyprogesterone,11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1966
1966
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Earlier studies in which direct comparisons were made between hyperplastic and adenomatous adrenal tissue showed little or no difference between steroid secretion patterns (24)(25)(26). Only D'Agata et al (27), studying the in vitro activities of several adrenocortical enzymes (not including 11/3-hydroxylase) in six adrenal adenomas, found increased 21-hydroxylase activity in adrenal adenomas compared with that in normal adrenal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in which direct comparisons were made between hyperplastic and adenomatous adrenal tissue showed little or no difference between steroid secretion patterns (24)(25)(26). Only D'Agata et al (27), studying the in vitro activities of several adrenocortical enzymes (not including 11/3-hydroxylase) in six adrenal adenomas, found increased 21-hydroxylase activity in adrenal adenomas compared with that in normal adrenal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although Race & Wu (1961) using whale tissue found that 17-oxosteroid concentrations in the zona reticularis were higher than those in other parts of the gland, and Ofstad, Lamvik, St0a & Emberland (1961) gave evidence for similar functional zonation in man, the work of Griffiths, Grant & Symington (1963) and Ward & Grant (1963) suggested that in man both the zona fasciculata and the z. reticularis can form testosterone and cortisol, and hence that these zones should be considered as a single functional unit. This view has been slightly modified by Jones & Griffiths (1968) who found that in guinea-pigs, sulphurylation of dehydroepiandrosterone may occur predominantly in the z. reticularis.…”
Section: Introductionmentioning
confidence: 99%
“…In man, dehydroepiandrosterone is a prominent secretory product, especially as the sulphate (Baulieu, 1965) while in incubation studies, testosterone has also been identified (Kase & Kowal, 1962;Ward & Grant, 1963). Other C19 steroids commonly found in adrenal studies of various species are androstenedione and 1 l/?-hydroxyandrostenedione (for review see Vinson & Whitehouse, 1970a).…”
Section: Introductionmentioning
confidence: 99%
“…The main difference was the presence of an active 16a-hydroxysteroid dehydrogenase. The reason for the increase in activity of this enzyme is obscure but 16a-hydroxy compounds are important in oestrogen metabolism (Breuer & Nooke, 1959;Levitz, Rosen & Twombly, 1960), as metabolites of progesterone (Villee, Dimoline, Engel, Villee & Racker, 1962;Ward & Grant, 1963) and in connexion with the postulated salt-losing hormone (Neher, Desaulles, Vischer, Wieland & Wettstein, 1958;Cope & Parry, 1959). Any or none of these possibilities may apply, but histological techniques do not allow us to discriminate between them.…”
Section: Discussionmentioning
confidence: 99%